136 Cardiac Involvement In Systemic Sclerosis: Strengths and Limitations of Cardiac Magnetic Resonance Imaging. (31st May 2014) - Webber, Matthew; Natarajan, Arun; Schreiber, Benjamin; Sanjay, Prasad; Schwaiger, Johannes; Handler, Clive; Coghlan, Gerry
Abstract : Introduction: Cardiac involvement is a well described complication in Systemic Sclerosis (SSc) and is considered to be one of the leading causes of mortality. Cardiac MRI (CMR) is an emerging tool that can add new information on fibrosis and inflammation. Its use in SSc is not well described and is limited to patients without known cardiac involvement. We therefore set out to evaluate CMR with respect to added diagnostic value, sensitivity and specificity in detecting abnormalities in a SSc population with heart disease. Methods: We collected data on all patients at the Pulmonary Artery Hypertension Unit, Royal Free Hospital London who were referred for CMR at the Royal Brompton Hospital between January 2000–2012. Clinical and CMR data was sourced from electronic medical records and patient notes. Known cardiac involvement was defined as a reduced ejection fraction (EF ≤45%) on echocardiogram, a raised pulmonary capillary wedge pressure (PCW ≥15 mmHg)/raised left ventricular end diastolic pressure (LVEDP ≥12 mmHg) on right heart catheterization, raised pulmonary artery pressure (mPAP ≥25 mmHg) or a raised troponin T (>0.014 mcg/l). A positive CMR scan was defined as positive late gadolinium enhancement (LGE), reduced EF (≥45%), reduced left ventricular long axis function (LVLAF), left ventricular hypertrophy or positive Short TI Inversion Recovery (STIR). Results: Seventy-eight patients were analysed in total; mean age was 56.0, 57 (73%) were female and 35 (45%) had diffuse SSc. In total CMR reported 340 abnormalities with the mean number of abnormalities per patient of 4.2. Forty-three patients (55%) were determined to have a positive CMR; 20 (25%) with positive LGE, 12 (15%) with reduced EF, 26 (33%) with reduced LVLAF, 18 (23%) with left ventricular hypertrophy and 1 patient with a positive STIR. Forty-nine patients (63%) had known cardiac involvement; 17 (22%) with a reduced EF, 33 (17%) with a raised PCW/LVEDP, 34 (44%) with a raised mPAP and 8 (10%) with a raised troponin T. In these patients 31 (63%) had significantly positive CMR scans and 18 (37%) had negative scans (p = 0.06 for difference). Overall CMR was determined to have 63% sensitivity and 58.6% specificity in detecting significant abnormalities in this group of patients. Conclusions: CMR is a safe and effective method for accurately assessing patients with scleroderma in a population with known and suspected cardiac involvement. It is able to detect previously unknown cardiac abnormalities such as LGE and it can add further diagnostic value with respect to LVLAF, which has not been documented before. Despite this, CMR currently lacks sensitivity in confirming known disease and the clinical value of the large number of minor abnormalities detected is not known. We call for prospective studies to determine the significance of CMR abnormalities in terms of diagnosis and prognosis of scleroderma heart disease.